Analisis Nilai-Nilai Pendidikan Pada Novel A+ Karya Ananda Putri Sebagai Bahan Ajar Pembelajaran Sastra Di SMA - Naufal, Muji Zain; Apriyanto, Ade; Mudiasih, Maylani (Universitas Nahdlatul Ulama Blitar, 2024)
The significance of education is a crucial value that is both instructive and practical for one's lifetime. Teachers can impart these principles to their students. Presently, there is a growing consensus that the importance of education should be given top priority, as the moral and ethical growth of pupils is being compromised by the prevalence of juvenile delinquency among them. The significance of education in daily life can be elucidated through literary compositions, specifically novels. This research was conducted to analyze the educational qualities depicted in the novel